The Alteration of Pro-inflammatory Cytokines and Oxidative Stress Markers at Six-Month Post-living Kidney Donation - Díaz-De la Cruz, Elodia Nataly; Cerrillos-Gutiérrez, José Ignacio; García-Sánchez, Andrés; Andrade-Sierra, Jorge; Cardona-Muñoz, Ernesto Germán; Rojas-Campos, Enrique; González-Espinoza, Eduardo; Miranda-Díaz, Alejandra Guillermina (Frontiers in Medicine, 2020)
Donors have a higher risk of developing chronic kidney disease than the general population. Some mechanisms mediated by pro-inflammatory cytokines and oxidative stress may be involved as risk factors. The objective of the study was to evaluate the behavior of pro-inflammatory cytokines and oxidative stress markers in living renal donors with a 6-month follow-up. A single prospective cohort was performed in 88 renal donors. At the end of the follow-up, the levels of lipoperoxides, 6.52±1.12 mM, and 8-isoprostanes, 63.75±13.28 pg/mL, were lower than before donation, 10.20±3.95 mM (p<0.001) and 67.54±9.64 pg/mL (p=0.026) respectively. Initial levels of nitric oxide (NO), 356.09±59.38 μM increased at the end of the follow-up, 467.08±38.74 μM (p<0.001). It was observed in the final determination of donors decreased activity of antioxidant enzymes superoxide dismutase (SOD), 0.74±0.57 U/L and glutathione peroxidase (GPx), 556.41±80.37 nmol, in comparison with the levels obtained in the initial determination, 1.05±0.57 U/L (p<0.001) and 827.93±162.78 nmol (p<0.001) respectively. The pro-inflammatory cytokines, Tumor necrosis factor alpha and interleukin-6 showed no differences at six months after donation. The enzyme oxoguanine glycosylase (hOGG1) responsible for repairing oxidative damage to DNA, showed a decrease in its concentration at the end of the study in donor men, 0.40±0.21 ng/mL compared to the initial levels, 0.55±0.32 ng/mL (p=0.025). The marker, 8-hydroxy-2-deoxyguanosine (8-OHdG) exhibited an increase in donor men at the final determination 2.28±1.99 ng/mL, compared to the concentration before donation, 1.72±1.96 ng/mL (p<0.001). We found significant changes in the markers of the oxidative state with increased NO and 8-OHdG, as well as a significant decrease in the antioxidant defenses SOD, GPx, and in the DNA repair enzyme in living renal donors after six months of follow-up.